Beauty and Function: The Use of Trimmed Great Toe in Thumb and Finger Reconstruction. Issue 9 (30th September 2022) - Troisi, Luigi; Mazzocconi, Luca; Mastroiacovo, Alessandro; Vizcay, Macarena; Zanchetta, Francesco; Stucchi, Sara; Pajardi, Giorgio Eugenio
Abstract : Background: Finger amputations are one of the most common traumas of daily life. Regularization of the digital stump is the most widely used option in the literature today. The aim of this study was to evaluate a valid functional and aesthetic alternative to amputation. Methods: We retrospectively investigated our prospective database‚ selecting the patients who underwent trimmed great toe flap reconstruction for the amputation of a digit from September 2019 to November 2021. All the operations were performed by the first author (L.T.) in the Reconstructive Microsurgery Service of the University Department of Hand Surgery and Rehabilitation of MultiMedica Group. Results: No flap required anastomosis revision or had major complications. The length of the amputated finger was maintained, with a high functional and aesthetic result achieved. Conclusions: The trimmed great toe flap has proven to be a viable alternative to finger amputation in the reconstruction of thumb and long finger defects, leading to high aesthetic results. The morbidity of the donor site is reduced compared with the classic great toe flap, allowing a direct closure in most cases.